Alteración lagrimal en paciente masculino de 22 años. - Alcántara Espinoza, Joel Denilson (2023)
Lacrimal disturbance or dry eye as it is known is when tears are unable to drain normally, causing the eyes to become irritated or watery. This is caused by a partial or complete obstruction in the tear secretion system. In this clinical case we proceed to perform a set of processes to a 22-year-old male patient who comes to optometric consultation for presenting burning, itching, red eyes and gritty sensation in the views, he mentions that for 6 months he has been using treatment for acne and the medication he uses is Isotretinoin. He means that he did research on this treatment and that as a side effect is the dryness of the mucosa, including the tear film. The main objective is to improve the patient's quality of life after the procedures performed by the ophthalmologist, when the treatment was started the ophthalmologist indicated that the evaporative dry eye syndrome or dry keratoconjunctivitis is something that can be treated very normally with proper control, hoping that the reactions to treatment are favorable, so that he can perform his daily activities without any complications. The patient showed that he felt well, and that he complied with the established treatment achieving the expected results.